ANALISIS PENGARUH HARGA, LUAS LAHAN, JAM KERJA, DAN MODAL TERHADAP PENDAPATAN PETANI KELAPA SAWIT DI KECAMATAN MENDAHARA KABUPATEN TANJUNG JABUNG TIMUR - Syafira Amelia; Haryadi; Candra Mustika (PT. Hasba Edukasi Mandiri, 2026)
This study aims to: 1) determine and analyze the socio-economic characteristics of oil palm farmers in Mendahara District, East Tanjung Jabung Regency. 2) determine and analyze the influence of price, land area, working hours and capital on the income of oil palm farmers in Mendahara District, East Tanjung Jabung Regency. The analytical method used in this study is quantitative descriptive analysis. Quantitative analysis tools use multiple linear regression using SPSS. The population in this study are oil palm farmers in Mendahara District, East Tanjung Jabung Regency. Sampling used a simple random sampling method, resulting in a sample of 93 oil palm farmers in Mendahara District. The results of this study indicate that: 1) The majority of oil palm farmers are male, with an average age of 46.8 years, an average of 9 years of junior high school education, with an average number of dependents of 3 people, with the majority owning their own farming businesses, with an average length of farming for 19 years, with an average capital of Rp. 15,583,064, average income of Rp. 12,566,129, with an average operating hours of 7-8 hours, with an average land area of 2.8 hectares, and an average selling price of Rp. 2,415. 2) The results of the research conducted stated that the variables of price, land area, working hours, and capital simultaneously have a significant effect on the income variable of oil palm farmers in Mendahara District, East Tanjung Jabung Regency. Partially, the price and working hours variables have a negative and significant effect on the income variable of oil palm farmers in Mendahara District, East Tanjung Jabung Regency, and the variables of land area and capital have a positive and significant effect on the income variable of oil palm farmers in Mendahara District, East Tanjung Jabung Regency.